Geographic Knowledge Discovery from Web 2.0 Technologies for Advance Collective Intelligence - Lee, I.; Torpelund-Bruin, C. (Informatica)
Geographic Knowledge Discovery from Web 2.0 Technologies for Advance Collective Intelligence